Seismic performance assessment of blind bolted steel-concrete composite joints based on pseudo-dynamic testing. (15th January 2017) - Wang, Jingfeng; Zhang, Huijie
Highlights: Pseudo-dynamic tests (PDTs) were performed on two full-scale blind bolted end-plate composite joints to CFTST columns. The influence of end-plate type and blind bolt extension on seismic behavior of CFTST column joints with concrete slab was investigated. Dynamic responses and failure modes of composite beam to CFTST column joints were analyzed in details. Abstract: This paper aims to investigate seismic behavior and dynamic responses of semi-rigid composite joints composed of steel-concrete composite beams and concrete-filled thin-walled steel tubular (CFTST) columns. A range of pseudo-dynamic tests (PDTs) was performed on two full-scale blind bolted end-plate joint specimens, including one flush and one extended end-plate typed joint. The input ground motion adopted for the PDTs was Ispara seismic acceleration record and scaled to represent various seismic hazard levels. Using Ispara earthquake record with different peak ground accelerations (PGAs), a lot of useful data about hysteresis behavior, stiffness degradation and energy dissipation capacity was obtained. The data was also estimated in detail to characterize the seismic performance of this kind of composite joints. Dynamic responses of beam-to-column joint including displacement and acceleration responses, and dynamic magnification factor were discussed. The experimental results indicated that the structural responses of the test joints under seismic actions coincided with the desired performances analyzed for varying damage levels. The study affirms that the blind bolted end-plate composite joints to CFTST columns possess good energy dissipation seismic performance, so they can provide sufficient ductility and adequate strength to satisfy the seismic design requirement.